2006
DOI: 10.1590/s0104-11692006000100003
|View full text |Cite
|
Sign up to set email alerts
|

Morbimortalidade por causas externas na população idosa residente em município da região sul do Brasil

Abstract: We analyzed morbidity and mortality rates due to external causes among elderly persons in a city in the South of Brazil. Data about deaths, from 1979 to 1998, and about hospital admissions, from 1995 to 1998, were obtained from the Mortality Information System and the Hospital Information System of the Brazilian Ministry of Health. Population data were based on the national demographic census. Mortality rates due to external causes decreased 16.2%, but levels increased in advanced ages, especially for women. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
27

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 9 publications
0
17
1
27
Order By: Relevance
“…Uma das prerrogativas em gerontologia é a manutenção da capacidade funcional e da autonomia entre os idosos, para manter suas atividades em uma sociedade em evolução 1 .…”
Section: Metodologiaunclassified
See 3 more Smart Citations
“…Uma das prerrogativas em gerontologia é a manutenção da capacidade funcional e da autonomia entre os idosos, para manter suas atividades em uma sociedade em evolução 1 .…”
Section: Metodologiaunclassified
“…Frente à nova estrutura etária da população brasileira, o envelhecimento populacional em curso sugere que a ocorrência de casos de violência entre a população idosa deva aumentar em nosso meio 1 .…”
Section: Metodologiaunclassified
See 2 more Smart Citations
“…One study (7) performed in Southern Brazil showed that hospitalizations due to falls represented the majority of the injuries registered in the Authorizations for Hospitalizations (AIHs, acronym for Autorizações de Internação Hospitalar): 62.5% of all thigh and hip traumas, 36% of lower limb traumas, 37.5% of head and neck, and 66.7% of other locations, such as thorax, abdomen and multiple traumas.…”
Section: Introductionmentioning
confidence: 99%